Here deprivation is born: The emergence of the vallejian poetic subject in Los heraldos negros - Sicard, Alain (Espergesia, 2019)
Under this title –that parodies Donde nace la lluvia, title given in 1960 by Neruda to the first volume of Isla Negra: A Notebook (1964)–, this work intends to analyse the emergence, in Los heraldos negros, of the theme of loss or deficiency, which, since Trilce, as I’ve tried in other occasions to show, confers on Cesar Vallejo’s poetry its unity and coherence.Many critics have judged harshly the modernist presence in The Black Heralds, reproaching it for being a hindrance to the genuine expression of the vallejan voice. This point of view will be discussed through a re-reading of «Retable». The last part of the poem introduces us to what will be the matrix of the theme of loss, to wit: the contradiction between religious faith and mortal experience, together with the crisis –illustrated by poems such as «Espergesia» or «Absolute»– that follows on. After which we’ll explore the repercussions of that crisis on the various thematic levels of the oeuvre: the absence of home, Americanity, the erotic experience, leaving open the conclusion on the posterity of loss as a theme in future books.